EFFECT OF RHIZOME SOAKING IN A MIXTURE OF Ba AND Ga3 ON THE EARLINESS OF FLOWERING AND QUALITY OF THE YIELD OF FLOWERS AND LEAVES IN THE CALLA LILY (Zantedeschia Spreng.) - Beata Janowska; Mateusz Stanecki (Acta Scientiarum Polonorum: Hortorum Cultus, 2013)
The effect of BA and GA3 on the yield and the quality of flowers and leaves of Zantedeschia was assessed in researches. The aim of the present research was to assess the effect of a mixture of benzyladenine and gibberellic acid in a solution used for rhizome soaking as well as of various duration times of this practice on the growth and flowering of the ‘Albomaculata’ and ‘Black Magic’ cultivars. In the experiment water solution containing benzyladenine at concentrations of 100, 350 and 600 mg·dm-3 was used combined with gibberellic acid at a concentration of 150 mg·dm-3. Rhizomes, 15–18 cm in circumference in 'Black Magic' cultivar and 20+ cm in 'Albomaculata' cultivar, with leaf buds 0.5–2 cm in length, were soaked for 30 and 60 minutes. Rhizome soaking in a BA and GA3 mixture increased the yield of flowers in the ‘Black Magic’ and ‘Albomaculata’ cultivars, but delayed their flowering, and the flowers developing from rhizomes had shorter peduncles. Besides, in ‘Black Magic’ cultivar the weight of flowers decreased. The application of a BA and GA3 mixture reduced the yield of leaves in ‘Albomaculata’ cultivar. However, they had a higher greenness index and a higher protein and sugar content.